Multiomic Approach for Bioprospection: Investigation of Toxins and Peptides of Brazilian Sea Anemone Bunodosoma caissarum - Mazzi Esquinca, Maria Eduarda [UNESP] (2023)
Sea anemones are sessile invertebrates of the phylum Cnidaria and their survival and evolutive success are highly related to the ability to produce and quickly inoculate venom, with the presence of potent toxins. In this study, a multi-omics approach was applied to characterize the protein composition of the tentacles and mucus of Bunodosoma caissarum, a species of sea anemone from the Brazilian coast. The tentacles transcriptome resulted in 23,444 annotated genes, of which 1% showed similarity with toxins or proteins related to toxin activity. In the proteome analysis, 430 polypeptides were consistently identified: 316 of them were more abundant in the tentacles while 114 were enriched in the mucus. Tentacle proteins were mostly enzymes, followed by DNA- and RNA-associated proteins, while in the mucus most proteins were toxins. In addition, peptidomics allowed the identification of large and small fragments of mature toxins, neuropeptides, and intracellular peptides. In conclusion, integrated omics identified previously unknown or uncharacterized genes in addition to 23 toxin-like proteins of therapeutic potential, improving the understanding of tentacle and mucus composition of sea anemones.